Cord blood: a new source of hematopoietic stem cells (Hematology Meeting Reports, 2009)
During the nearly 40 years elapsed since the first successful bone marrow transplantation, significant improvements have been registered in the field of allograft, also in connection with the use of cord blood as a source of hematopoietic stem cells. The number of cord blood transplants is increasing worldwide with the establishment of related and unrelated cord blood banks. The incidence of both acute and chronic graft-versus-host disease, the most important and life-threatening immune complications after transplantation, is significantly reduced with cord blood grafts and, in view of this fact, cord blood transplantation offers the opportunity of using HLA-disparate donors. This latter finding, together with the immediate availability of cryopreserved cells, is the main advantage for children who lack an HLA-identical sibling and who need transplantation from an unrelated donor. Moreover, in patients with hematological malignancies, the rate of relapse appears to be similar to that documented in bone marrow transplant recipients. The main limitation related to cord blood transplantation is represented by the number of cells available in a single unit which has so far restricted the use of cord blood as source of hematopoietic stem cells mainly to children. Approaches aimed at increasing the number of cells/hematopoietic progenitors infused, such as transplanting two units in the same patient or ex vivo expanding cord blood hematopoietic stem cells, could further increase in the future the number of cord blood transplantation performed every year.